A Patient Preference Study that Evaluated Fluticasone Furoate and Mometasone Furoate Nasal Sprays for Allergic Rhinitis. Issue 4 (October 2016) - Yanez, Anahi; Dimitroff, Alex; Bremner, Peter; Rhee, Chae-Seo; Luscombe, Graham; Prillaman, Barbara A.; Johnson, Neil
Background: Corticosteroid nasal sprays are the mainstay of treatment for allergic rhinitis. These sprays have sensory attributes such as scent and/or odor, taste and aftertaste, and run down the throat and/or the nose, which, when unpleasant, can affect patient preference for, and compliance with, treatment. Objective: This study examined patient preference for fluticasone furoate nasal spray (FFNS) or mometasone furoate nasal spray (MFNS) based on their sensory attributes after administration in patients with allergic rhinitis. Methods: This was a multicenter, randomized, double-blind, cross-over study. Patient preferences were determined by using three questionnaires (Overall Preference, Immediate Attributes, and Delayed Attributes). Results: Overall, 56% of patients stated a preference for FFNS versus 32% for MFNS (p < 0.001); the remaining 12% stated no preference. More patients stated a preference for FFNS versus MFNS for the attributes of "less drip down the throat" (p < 0.001), "less run out of the nose" (p < 0.05), "more soothing" (p < 0.05), and "less irritating" (p < 0.001). More patients responded in favor of FFNS versus MFNS for the immediate attributes, "run down the throat" (p < 0.001), and "run out of the nose" (p < 0.001), and, in the delayed attributes, "run down the throat" (p < 0.001), "run out of the nose" (p < 0.01), "presence of aftertaste" (p < 0.01), and "no nasal irritation" (p < 0.001). Conclusion: Patients with allergic rhinitis preferred FFNS versus MFNS overall and based on a number of individual attributes, including "less drip down the throat, " "less run out of the nose, " and "less irritating." Greater preference may improve patient adherence and thereby improve symptom management of the patient's allergic rhinitis.